The last man : a thriller - Flynn, Vince (New York : Emily Bestler Books/Atria, 2012)
When a CIA black ops master with ties to disreputable figures in Afghanistan goes missing, Mitch Rapp is ordered to track down the missing man at all costs and finds himself enmeshed in a dangerous plot involving the interests of numerous countries.
Keywords: United States. -- Central Intelligence Agency -- Officials and employees -- Fiction; Rapp, Mitch (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Missing persons -- Fiction; Terrorism -- Prevention -- Fiction; Afghanistan -- Fiction; Political fiction; Suspense fiction